2003
DOI: 10.1152/japplphysiol.00364.2002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inspiratory muscle strength training on inspiratory motor drive and RREP early peak components

Abstract: . Effect of inspiratory muscle strength training on inspiratory motor drive and RREP early peak components. J Appl Physiol 94: 462-468, 2003. First published September 20, 2002 10.1152/japplphysiol.00364.2002This study investigated the effect of inspiratory muscle strength training (IMST) on inspiratory motor drive [mouth occlusion pressure at 0.1 s (P0.1)] and respiratory-related evoked potentials (RREP). It was hypothesized that, if IMST increased inspiratory muscle strength, inspiratory motor drive would d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 38 publications
4
41
1
3
Order By: Relevance
“…Thus, it seems that reduced respiratory muscle strength increases inspiratory motor drive, which in turn results in an increase in respiratory sensitivity. 22 Hence, the major factor determining inspiratory muscle weakness is the magnitude of the ratio between the inspiratory pressure demand (P 0.1 ) and the maximal inspiratory pressure (P Imax ). P 0.1 /P Imax ratio reflects a balance between the magnitude of the respiratory load and the muscle strength available to meet the load.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it seems that reduced respiratory muscle strength increases inspiratory motor drive, which in turn results in an increase in respiratory sensitivity. 22 Hence, the major factor determining inspiratory muscle weakness is the magnitude of the ratio between the inspiratory pressure demand (P 0.1 ) and the maximal inspiratory pressure (P Imax ). P 0.1 /P Imax ratio reflects a balance between the magnitude of the respiratory load and the muscle strength available to meet the load.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it seems that reduced respiratory muscle strength increases inspiratory motor drive, which in turn results in an increase in respiratory sensitivity. 29 Occlusion pressure is the pressure generated in the airway by contraction of inspiratory muscles when the airway has been occluded at end-expiration. P 0.1 was introduced so as to distinguish hypoventilation due to high pulmonary resistance or elastance from hypoventilation due to respiratory pump failure (as seen in obese subjects).…”
Section: Discussionmentioning
confidence: 99%
“…However, measuring respiratory muscle pressure at the mouth, as was performed in our study, has been shown to elicit similar effects as BPNS and been used in many previous studies (Huang et al, 2003;Inbar et al, 2000;Romer, McConnell, & Jones, 2002a;Romer, McConnell, & Jones, 2002b;Sonetti et al, 2001). Since P Imax maneuvers are effort-dependent, subjects in our study were highly encouraged to perform maximal effort, tests were made in triplicate, and lung volume measures were made with each trial to ensure consistency.…”
Section: Limitationsmentioning
confidence: 81%
“…Maximal inspiratory pressure (P Imax ) was measured from RV and maximal expiratory pressure (P Emax ) was measured from TLC. P Imax and P Emax are measurements of respiratory muscle strength measured at the mouth and have been shown to be a good estimate of respiratory muscle strength (Huang, Martin, & Davenport, 2003;Inbar, Weiner, Azgad, Rotstein, & Weinstein, 2000; during the discontinuous bouts when P Imax and P Emax were measured in duplicate due to time constraints. The average values of acceptable trials were used in analysis.…”
Section: Pulmonary Function Testsmentioning
confidence: 99%